Children's reading profiles on exiting the Reading Recovery programme: do they predict sustained progress?. (21st December 2014) - Holliman, Andrew J.; Hurry, Jane; Bodman, Sue
Abstract : The aim of this study was to identify reading profiles, which predict the literacy progress of Reading Recovery graduates. Reading Recovery is an intensive remediation for children after the first year of school. Children were assessed at exit from the programme and at 3‐month, 6‐month and 12‐month follow‐up points. Text Reading Level made unique contributions to word reading, spelling and writing at all time points and was consistently the best predictor of word reading. Phonological processing also made unique contributions to word reading and spelling. Reading comprehension was found to be the best predictor of National Curriculum sublevels for reading and writing, 12 months later. These findings indicate that levelled texts, as employed in Reading Recovery, provide a good indication of progress in word reading, spelling and writing after the programme has been discontinued, but also present a case for assessing other reading skills (e.g., phonological processing and reading comprehension) in order to help predict sustained progress in literacy.